Mapping the multiple intersectoral spaces for civil society participation and responsiveness strengthening in the South African health system – focusing on the Western Cape - Whiting, Amy (Department of Public Health and Family Medicine, 2022)
Since the Alma Ata Declaration of 1978, community participation in health policy development and health system functioning has called for a collaborative intersectoral approach, engaging civil society as a pivotal agent for improving policy-makers' responsiveness in the public health system. Intersectoral approaches are widely accepted and research has shown the value in engaging communities in the improvement of their health. However, astonishingly little is known about the overall configuration, nature, and focus of the ‘spaces' where civil society are participating in health system-relevant engagement, or their contribution towards improved system responsiveness. This study describes a local provincial health system, the Western Cape province in South Africa, mapping the intersectoral spaces where civil society participates in the health system, provides feedback to the system (towards responsiveness), and contributes to health system improvement decisions. A mixed method case study was conducted, integrating desk-based review of multiple forms of openly available data, with verification from experts in the field. Sixteen intersectoral spaces in the Western Cape health system were mapped and compared, with analysis focussing on current governance practices in these spaces, evidence of accountability measures and civil society participation within the broader goal of improving health system responsiveness. Multiple spaces exist for intersectoral engagement in the Western Cape of South Africa, but there is a lack of any ‘system-wide' integrative approach – which creates overlap, a focus on vertical programming, and parts of civil society remain ‘disconnected' from the system. Feedback from civil society back into national or provincial policy-making processes is sporadic due to fragmented tiered governance. New efforts towards ‘whole-system' intersectoral collaboration need to be initiated and actively protected, if they are to succeed. This study demonstrates that while ‘intersectoral action for responsiveness strengthening' is broadly encouraged in this health system, it needs to be more fully assessed and operationalised in terms of multilevel governance, accountability and civil society empowerment. In doing so avenues can be identified for improving civil society's feedback into the public health system, and ensuring adequate system's response to this feedback, in health policy and practice.